Pengaruh Komitmen Organisasi, Self Eficacy, dan Servant Leadership Terhadap Kepuasan Kerja Karyawan di Minimarket Sebelas Q’Ta Temanggung - Hidayat, Wahyu (Universitas Islam Kadiri, 2025)
This study aims to analyse the effect of Organisational Commitment, Self Eficacy, and Servant Leadership on Employee Job Satisfaction at Eleven Q'Ta Temanggung Minimarket. The research method conducted by researchers uses quantitative methods. The object of this research is the employees of Minimarket Sebelas Q'Ta Temanggung. The sample in this study amounted to 40 respondents with data analysis using the SPSS application. The results showed that all variables were found to be significantly positive towards employee job satisfaction.